Serious game for physical rehabilitation: measuring the effectiveness of virtual and real training environments - Postolache, O. (2017)
Recent advances in low-cost natural user interfaces such as Microsoft Kinect and Leap Motion controller allow the Virtual Reality implementation of 3D serious games for, posture, upper limb and lower limb rehabilitation purposes. However, it is very important to compare the results obtained by the users that train in virtual and real environments. This paper presents a virtual reality serious game for upper limb rehabilitation using a natural user interface expressed by Leap Motion controller. One of the developed virtual reality serious game for rehabilitation is converted to a real scenario with the same elements and rules and the same aims of physical rehabilitation. In order to extract appropriate information from the serious game based on real objects a RFID technology was used together with software components developed in LabVIEW. The evaluation of hand muscles' activity during the training session is based on the usage of thermography that permits to measure in an unobtrusive way the distribution of the temperature on the hands' level. Based on analysis of thermographic images obtained before and after serious game practice, the level of activity of specific muscles associated with training for virtual and real scenario is extracted. Experimental results that are also included in the paper underline the effectiveness of the proposed method for the comparison of the training in virtual and real scenarios.